2017
DOI: 10.1016/j.nano.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating peptide CGKRK mediates efficient and widespread targeting of bladder mucosa following focal injury

Abstract: The bladder presents an attractive target for topical drug delivery. The barrier function of the bladder mucosa (urothelium) presents a penetration challenge for small molecules and nanoparticles. We found that focal mechanical injury of the urothelium greatly enhances the binding and penetration of intravesically-administered cell-penetrating peptide CGKRK (Cys-Gly-Lys-Arg-Lys). Notably, the CGKRK bound to the entire urothelium, and the peptide was able to penetrate into the muscular layer. This phenomenon wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Peptides, especially membrane-active cationic peptides capable of transducing the cell membrane, have been vastly studied as delivery vectors for intracellular cargo delivery. Even though it can be touted as a simple and effective strategy, they are yet to be established as drug delivery vectors for clinical applications. This has been majorly due to the poor half-life in biological systems attributable to premature proteolytic cleavage in the presence of biological tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides, especially membrane-active cationic peptides capable of transducing the cell membrane, have been vastly studied as delivery vectors for intracellular cargo delivery. Even though it can be touted as a simple and effective strategy, they are yet to be established as drug delivery vectors for clinical applications. This has been majorly due to the poor half-life in biological systems attributable to premature proteolytic cleavage in the presence of biological tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Griffin et al found the peptide CGKRK (Cys-Gly-Lys-Arg-Lys) could penetrate mucosal layers following focal mechanical damage to the urothelium [ 122 ]. After the focal injury, the intravesical peptide could bind to the entire urothelium, further penetrating the deeper tissues than the control without the injury treatment.…”
Section: Physical Methods To Get Drugs Across Bladder Penetrating mentioning
confidence: 99%
“…Induces cell recruitment through receptor-influenced endocytosis (Wang et al, 2017a). Providing the ability to deliver various drugs, from anticarcinogens and peptides (Griffin et al, 2017;Li et al, 2021). Several reactions allow the formation of such microgels and nanogels, among them are the thiol-ene chemistry mediated by radicals, the photo-click chemistry of tetrazole-alkene, the oxime, the Dielse-Alder Reaction and the azide cycloaddition, strainpromoted alkyne (Palmese et al, 2019).…”
Section: Hgs Functionalized With Nano and Micromaterialsmentioning
confidence: 99%